2016
DOI: 10.1016/j.cmi.2015.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline of fasting glucose in HCV diabetic patients treated with direct-acting antiviral agents

Abstract: Association between hepatitis C virus (HCV) infection and diabetes has been widely postulated. Little is known about the effect of direct-acting antiviral agents (DAAs) on glycaemic control. The aim of our study was to evaluate the glycaemic control modifications in a case series of HCV-positive diabetic patients receiving DAAs. We retrospectively evaluated 149 HCV-positive patients in two different institutions affiliated with Sapienza University: Policlinico Umberto I of Rome and Ospedale Santa Maria Goretti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 6 publications
10
71
0
Order By: Relevance
“…This is in agreement with several studies [12,[15][16][17]. Abdel Alem et al, found a reduction in both FBS and HbA1c after HCV eradication [18].…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with several studies [12,[15][16][17]. Abdel Alem et al, found a reduction in both FBS and HbA1c after HCV eradication [18].…”
Section: Discussionsupporting
confidence: 82%
“…5 after SVR is attained using DAA therapy. Similar results are recently published using other treatment regimens (9,31). The reversibility of hypocholesterolemia, hypotriglyceridemia, and hepatic steatosis is demonstrated after the attainment of SVR in therapy regimens based on interferon (32)(33)(34).…”
Section: Discussionsupporting
confidence: 75%
“…Recent data suggest that HCV infection directly impairs glucose metabolism and contributes to insulin resistance [2]. Treatment of genotype 1 HCV infection with interferon based regimens or direct acting antiviral agents (DAAs) has correlated with improved insulin sensitivity and glycemic control in both insulin dependent and noninsulin dependent T2DM [37]. We report a case of mixed genotype 1a/1b HCV infection with compensated cirrhosis treated with DAAs resulting in significant improvement of poorly controlled T2DM despite increasing body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%